Long-Term Patient-Reported Outcomes After Radiofrequency Ablation and Cryoballoon Ablation for Paroxysmal Atrial Fibrillation: The Effect of Additional Ablations - Ibrahim Antoun; Ahmed I. Kotb; Zakkariya Vali; Ahmed Abdelrazik; Ivelin Koev; Kassem Safwan; Edward Y. M. Lau; Riyaz Somani; Ghulam André Ng (Journal of Cardiovascular Development and Disease, 2024)
Background: pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation (PAF) improves health-related quality of life (QoL). This study compares QoL improvement after radiofrequency ablation (RF) and cryoballoon ablation (cryo) and assesses additional ablations’ role in QoL improvement. Methods: we evaluated the QoL of consecutive patients with first-time RF and cryo for PAF between January 2017 and June 2019. A combined EQ-VAS, AFEQT, and EQ-5D-3L paper questionnaire was sent to patients at baseline, 12, and 30 months after the procedure. Procedure and patient details were collected from medical notes. Results: the analysis included 207 patients, of which 127 (61%) had RF and 144 (70%) were males. RF patients had more additional ablations (52 [41%] versus 22 [28%], p = 0.01). There was a significant improvement from baseline to 12 months post-RF in AFEQT (43 ± 9 to 83 ± 7.8, p < 0.001), EQ-5D-3L (−0.01 ± 0.01 to 1.1 ± 0.02, p < 0.001), and EQ-VAS (51 ± 8 to 77 ± 13, p = 0.01). Similarly, an improvement at 12 months was observed after cryo in AFEQT (55 ± 11 to 77 ± 9, p < 0.001), EQ-5D-3L (−0.04 ± 0.03 to 1.3 ± 0.03, p < 0.001), and EQ-VAS (56 ± 7 to 85 ± 9, p = 0.01). QoL improvement was similar between RF and cryo. Additional ablations provided no additional QoL improvement compared to patients with PVI alone. Conclusions: Patients undergoing first-time PVI for PAF, RF, and cryo showed similar QoL improvement at 12 months, which was sustained at 30 months. Additional ablations did not provide further QoL benefits.